A pharmacovigilance study of anti-depressant agents in psychiatric patients at a tertiary care teaching hospital - Bhushan, D. Phani; Babu, R. Hari; Rashi, J.; Suvidha, M. Tabitha Satya; U., Mounika Susanthi; Lekha, T. Sri (International Journal of Research in Medical Sciences, 2020)
Background: Anti-depressant drugs have great benefit in treating a many psychiatric disorders, including schizophrenia and bipolar disorder, although all these drugs are associated with many potential adverse effects. In this study, the occurrence of adverse effects like weight gain, sleep disturbances, dry mouth were assessed and reported in drug naïve patients Anti-depressant drugs. Methods: It is a prospective observational study of patients attending Psychiatry department in NRI General Hospital of age 10 to 80 years who were prescribed with anti-depressant drugs. The study was conducted for a period of 8 months from June 2018 to February 2018. Results: Among 86 patients prescribed with antidepressants, the occurrence of adverse drug reactions due to antidepressants was 60.78% with Selective serotonin reuptake inhibitors being the most common class of drugs implicated for adverse drug reactions followed by 24.49% with Tricyclic antidepressants. A total of 51 adverse drug reactions were noted of which weight gain was most common, closely followed by sleep disturbances and drowsiness. Out of 52 adverse drug reactions assessed for causality, 88.2% of the adverse drug reactions cases were probable, while 11.7% were possible. According to Hartwig and Siegel’s Scale 84.3% of the cases are found to be mild, 15.68% moderate. Conclusions: The study allows knowing information about the occurrence and pattern of adverse drug reactions associated with Anti-depressant drugs in the population thus reducing its incidence and protecting the user population from available harm.